Vascular Endothelial Growth Factor‐121 Administration Mitigates Halogen Inhalation‐Induced Pulmonary Injury and Fetal Growth Restriction in Pregnant Mice. Issue 3 (4th February 2020) - Addis, Dylan R.; Lambert, James A.; Ren, Changchun; Doran, Stephen; Aggarwal, Saurabh; Jilling, Tamas; Matalon, Sadis
Abstract : Background: Circulating levels of sFLT‐1 (soluble fms‐like tyrosine kinase 1), the extracellular domain of vascular endothelial growth factor (VEGF) receptor 1, and its ratio to levels of placental growth factor are markers of the occurrence and severity of preeclampsia. Methods and Results: C57BL/6 pregnant mice on embryonic day 14.5 (E14.5), male, and non‐pregnant female mice were exposed to air or to Br2 at 600 ppm for 30 minutes and were treated with vehicle or with VEGF‐121 (100 μg/kg, subcutaneously) daily, starting 48 hours post‐exposure. Plasma, bronchoalveolar lavage fluid, lungs, fetuses, and placentas were collected 120 hours post‐exposure. In Br2 ‐exposed pregnant mice, there was a time‐dependent and significant increase in plasma levels of sFLT‐1 which correlated with increases in mouse lung wet/dry weights and bronchoalveolar lavage fluid protein content. Supplementation of exogenous VEGF‐121 improved survival and weight gain, reduced lung wet/dry weights, decreased bronchoalveolar lavage fluid protein levels, enhanced placental development, and improved fetal growth in pregnant mice exposed to Br2 . Exogenous VEGF‐121 administration had no effect in non‐pregnant mice. Conclusions: These results implicate inhibition of VEGF signaling driven by sFLT‐1 overexpression as a mechanism of pregnancy‐specific injury leading to lung edema, maternal mortality, and fetal growth restriction after bromine gas exposure.